Pengaruh Kemudahan dan Keamanan Transaksi Penggunaan Mobile Banking terhadap Keputusan Pembelian Online - Jayadi, Jayadi; Risnawati, Risnawati; Muslimin, Muslimin (Journal of Business Administration (JBA), 2024)
This research is aimed to investigate the influence of transaction ease and security in mobile banking on online purchasing decisions. The population of the research was 6,447 students the state polytecnic of ujung pandang. The Sampling technique used is probability sampling with the Stratified random sampling. The sample of this research was 98 students. The data collection method used interviews and questionnaires. The data analysis used instrument validation, descriptive statistics, and inferential statistics by using statistical package for social sciences (SPSS) software version 25 for windows. The results of this research showed that 1) the perception of customer the ease of used mobile banking was very easy, 2) the perception of customer the security of transactions used mobile banking was very safe, 3) the perceptions of customer online purchasing decisions used mobile banking was very good, 4) ease of use has significant effect on online purchasing decisions used mobile banking, 5) transaction security has significant effect on online purchasing decisions used mobile banking, 6) ease and security of transactions has significant effect on online purchasing decisions used mobile banking.